Evil angels and forensic scientists : representations of law in popular culture - V. Rivalland (Law Text Culture, 1995)
Professor Chase (1986: 527) suggests law would benefit if it recognised and gave serious study to 'the impact of legal ideas conveyed through the' institutions of popular culture'. In responding to his challenge I intend to address just one aspect of law's representation in popular culture, the law/science nexus through its manifestation as forensic science. That area relates directly to the role and status of these intersecting discourses, and raises the question of whether the hierarchy of discourses which gives natural precedence to science adversely affects law. In other words, is justice a casualty in these encounters? In examining this proposition, I have selected two texts with contrasting representations of science's role in law.